The assessment of impact of «Kirovskaya» mine on the state of a soil and plant cover of the industrial site - Starikova, A.E.; Zernke, B. (Fundamental and Experimental Biology, 2015)
In the article technogenic influence of Kirovskaya mine on a soil and plant cover of a sanitary protection zone of the enterprise is considered. During the analysis it was revealed that the selected tests of soils contain the significant amount of the heavy metals exceeding maximum permissible concentration. The analysis showed that great values reach such substances as chrome, copper, zirconium, zinc and nickel. Migration and accumulation by plants of substances of the 1–2 classes of danger in high values were set. Active migration from soil into plants is observed in such metals as boron, copper, chrome, zinc. Manifestation of toxic effect of heavy metals happens, as a rule, at a top level of anthropogenic pollution of soils by them and in many respects depends on properties and peculiarities of behavior of concrete metal.